The role of socio-economic status and perinatal factors in racial disparities in the risk of cerebral palsy - Durkin, Maureen S (Dev Med Child Neurol, 2015)
AIM: To determine whether racial disparities in cerebral palsy (CP) risk among US children persist after controlling for socio-economic status (SES) (here indicated by maternal education) and perinatal risk factors. METHOD: A population-based birth cohort study was conducted using the Autism and Developmental Disabilities Monitoring Network surveillance and birth data for 8-year-old children residing in multi-county areas in Alabama, Georgia, Missouri, and Wisconsin between 2002 and 2008. The birth cohort comparison group included 458 027 children and the case group included 1570 children with CP, 1202 with available birth records. χ(2) tests were performed to evaluate associations and logistic regression was used to calculate relative risks (RR) and adjusted odds ratios (OR) with 95% confidence intervals (CI). RESULTS: The risk of spastic CP was more than 50% higher for black versus white children (RR 1.52, 95% CI 1.33–1.73), and this excess risk persisted after adjustment for SES (OR 1.35, 95% CI 1.18–1.55), but not after further adjustment for preterm birth and size for gestational age. The protective effect of maternal education remained after adjustment for race/ethnicity and perinatal factors. INTERPRETATION: Maternal education appears to independently affect CP risk but does not fully explain existing racial disparities in CP prevalence in the US.